2002
DOI: 10.1021/jm010375a
|View full text |Cite
|
Sign up to set email alerts
|

Minor Groove DNA Binders as Antimicrobial Agents. 1. Pyrrole Tetraamides Are Potent Antibacterials against Vancomycin Resistant Enteroccoci and Methicillin Resistant Staphylococcus aureus

Abstract: A new series of short pyrrole tetraamides are described whose submicromolar DNA binding affinity is an essential component for their strong antibacterial activity. This class of compounds is related to the linked bis-netropsins and bis-distamycins, but here, only one amino-pyrrole-carboxamide unit and an amidine tail is connected to either side of a central dicarboxylic acid linker. The highest degree of DNA binding, measured by compound-induced changes in UV melting temperatures of an AT-rich DNA oligomer, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 29 publications
4
64
0
1
Order By: Relevance
“…With the increase in the concentration of Tat (49-57), when the groove of ct-DNA was padded by Tat (49-57), the interaction of side chains containing guanidine and amino groups of Tat (49-57) destabilized the base pairs of DNA, caused the aromatic bases to become exposed, and resulted in hyperchromism of DNA [22] . The structure of Tat (49-57) very closely resembles DNA minor groove binders netropsin [23,35] , possessing positive charges and linearity. Therefore, according to the experimental data, minor groove binding interactions might have occurred …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase in the concentration of Tat (49-57), when the groove of ct-DNA was padded by Tat (49-57), the interaction of side chains containing guanidine and amino groups of Tat (49-57) destabilized the base pairs of DNA, caused the aromatic bases to become exposed, and resulted in hyperchromism of DNA [22] . The structure of Tat (49-57) very closely resembles DNA minor groove binders netropsin [23,35] , possessing positive charges and linearity. Therefore, according to the experimental data, minor groove binding interactions might have occurred …”
Section: Resultsmentioning
confidence: 99%
“…The side chains of Tat (49-57) have two cationic tail groups (guanidine). The structural features of Tat (49-57) are similar to head-to-head pyrrole tetraamides [34,35] , that can display antibacterial activity and also bind to the minor groove of DNA. Several other studies also revealed that agents that can bind to DNA.…”
Section: Resultsmentioning
confidence: 99%
“…The situation at hand, therefore, warrants the development and/or use of novel antibiotics to combat these resilient pathogens. While the quest for new antimicrobials, including peptides, goes on (7,16,24,28,35), there is at least one existing antimicrobial agent with as-yet-untapped potential-triclosan.…”
mentioning
confidence: 99%
“…The preparation starts, therefore, with the dilithiation of 2,5-dibromotoluene with t-BuLi at -78 8C, followed by reaction with dry ice and subsequent acidification, leading to the introduction of the two carboxyl groups. [8] The resultant 2-methylterephthalic acid (3) is esterified, [9] then side-chain brominated with NBS, to produce dimethyl 2-bromomethylterephthalate (4). [9,10] Compound 4 is then subjected to treatment with aqueous Na 2 SO 3 , in the presence of Bu 4 NBr as catalyst, in a process of nucleophilic replacement of bromine by a sulfonate anion.…”
Section: Preparation Of 2-sulfomethylterephthalic Acid (1)mentioning
confidence: 99%